Protective effect of Panax ginseng extract on cisplatin-induced AKI via downregulating cell death associated genes - Reza Alipanah-Moghadam; Vahideh Aghamohammadi; Sina Seifi; Hedieh Esmaeili; Somaieh Noroozzadeh; Farhad Jeddi; Ramin Salimnejad; Ali Nemati (Scientific Reports)
Abstract This study is designed to assess the effect of root extract of P. ginseng on kidney tissue injury attributed to cisplatin and its molecular mechanism involved in this process in the AKI rat model. Twenty-four male Wistar rats were randomly allocated into 4 experimental groups including: the control group, the cisplatin group, the extract 100 mg/kg group, and the extract 200 mg/kg group. The duration of the investigation was 7 days, and all rats except the control group received a single dose of 10 mg/kg cisplatin on the 4th day. Our findings exhibited a significant reduction in blood concentration of creatinine in extract groups compared to the cisplatin group. In the cisplatin group, severe renal histopathological alterations were observed compared to the control group. In extract groups, significantly less tissue damage was observed than in the cisplatin group. Ginseng extract 200 showed minimal tissue damage as compared to extract 100. The expression of p21, p27, p53, TIMP2, IGFBP7, and NF-κB decreased significantly in extract groups compared to the cisplatin group. Our findings displayed amelioration of cisplatin-induced AKI and dose-dependent decrease of the NF-κB gene expression and cell death-inducing genes by administration of P. ginseng extract.